PENGENDALIAN SOSIAL OLEH KONSELOR PADA RESIDEN (MANTAN PECANDU NARKOBA) DI PANTI REHABILITASI INSTITUSI PENERIMA WAJIB LAPOR TERATAI KAHATULISTIWA KUBU RAYA - Bagus Satria; Rustiyarso Rustiyarso; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this researched to find out the form of social control by counselors to residents who are in Institusi Penerima Wajib Lapor Teratai Khatulistiwa Kubu Raya. The method used in this researched qualitative approached with descriptive methods. The data sources in this study were counselors and residents in the institution. The results showed that: (1) Preventive social control carried out by counselors to residents at IPWL Teratai Khatulistiwa is good because counselors always educate and remind about applicable regulations and provided rewards to residents who behaved well or do not violate the rules. (2) Coercived social control carried out by counselors to residents at IPWL Teratai Khatulistiwa is good because the counselors give punishment or sanctions to residents who violate the form of sanctions to clean shared facilities and written outcomes. Meanwhile, the form of control with a warning is in the form of reminding to give a shock therapy. (3) The repressive social control carried out by the counselor to the resident at IPWL Teratai Khatulistiwa good because the counselor has provided advice and psychological sanctions such as reminding and giving chair punishment.Keywords: Rehabilitation , Social Control.